2018
DOI: 10.1002/marc.201800018
|View full text |Cite
|
Sign up to set email alerts
|

Photoregulating of Stretchability and Toughness of a Self‐Healable Polymer Hydrogel

Abstract: Supramolecular hydrogels that are assembled through dynamic host-guest interactions have presented apparent potential in the construction of materials with promising performance. Herein, a photoregulated hydrogel cross-linked by host-guest interactions with multifunctions of high stretchability, strong toughness, and rapid self-healing property is reported. The hydrogel exhibits unique light-responsive property due to the introduction of two photoisomerized groups. For example, the stress-strain curve of the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…(a represents the hydrogel after UV irradiation). b) Comparison of mechanical properties of photochromic hydrogels doped with different photochromic molecules, e.g., lanthanide ions, [ 32,33 ] polymetallic oxides, [ 34,35 ] diarylvinyl, [ 36 ] azobenzene, [ 37 ] and spiropyran. [ 38–41 ]…”
Section: Resultsmentioning
confidence: 99%
“…(a represents the hydrogel after UV irradiation). b) Comparison of mechanical properties of photochromic hydrogels doped with different photochromic molecules, e.g., lanthanide ions, [ 32,33 ] polymetallic oxides, [ 34,35 ] diarylvinyl, [ 36 ] azobenzene, [ 37 ] and spiropyran. [ 38–41 ]…”
Section: Resultsmentioning
confidence: 99%
“…We observed that as-made hydrogels exhibited initial tensile moduli of ∼815 kPa, which is among the strongest supramolecular hydrogels with healing ability as compared with other recently reported self-healing materials with comparable healing times (Table S1). We found that upon severing the hydrogels and healing for 24 h, the initial tensile modulus was similar at 785 ± 40 kPa.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a photoregulated photochromic hydrogel formed of spiropyran functionalised polyacrylamide (PAM) chain, decorated with azobenzene and β-CD pendant groups that could self-heal within 10 s was reported. 173 Toughness of the hydrogel was controlled by dynamic host-guest interaction between cyclodextrin and azobenzene as azobenzene isomerises upon irradiation with light ( Fig. 25).…”
Section: Hydrogelsmentioning
confidence: 99%